2020
DOI: 10.1071/sr20007
|View full text |Cite
|
Sign up to set email alerts
|

Carbon sequestration and selected hydraulic characteristics under conservation agriculture and traditional tillage practices in Malawi

Abstract: Conservation agriculture (CA) is increasingly promoted among smallholder farmers of sub-Saharan Africa in a quest to improve food security while sustaining the natural resource base of the agro-ecosystems where agriculture is based. The aim of this study was to investigate the effects of CA and traditional tillage on soil organic carbon (SOC) and selected hydraulic properties in two contrasting agro-ecological zones of Malawi. Six farmers hosted on-farm trials in each location, with each farmer having the foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…The results obtained here agree with literature findings suggesting increases in SOC stocks in no-till systems (Dey et al, 2020;Duval et al, 2020;Gonçalves et al, 2019;Yang & Wander, 1999) and Maris et al, (2021) who showed highly significant enrichment of SOC stocks in systems employing leguminous cover crops. Our results suggesting improvements in SOC and other soil properties under CA, also agree with findings in other studies in Malawi (Mloza-Banda et al, 2014 and on sites with CA having been implemented for up to 10 years (Simwaka et al, 2020). Yet our results contradict findings from a number of locations in southern Africa on which CA had been implemented for up to seven years where no significant differences in SOC stocks between CA and conventional till systems were observed (Cheesman et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…The results obtained here agree with literature findings suggesting increases in SOC stocks in no-till systems (Dey et al, 2020;Duval et al, 2020;Gonçalves et al, 2019;Yang & Wander, 1999) and Maris et al, (2021) who showed highly significant enrichment of SOC stocks in systems employing leguminous cover crops. Our results suggesting improvements in SOC and other soil properties under CA, also agree with findings in other studies in Malawi (Mloza-Banda et al, 2014 and on sites with CA having been implemented for up to 10 years (Simwaka et al, 2020). Yet our results contradict findings from a number of locations in southern Africa on which CA had been implemented for up to seven years where no significant differences in SOC stocks between CA and conventional till systems were observed (Cheesman et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…Southern Africa has been under a dark cloud of adverse weather conditions for the past 4 decades (SHEPPARD et al, 2020) and it seems likely that the situation will change for the better. Projections by climate experts predict future negative impacts owing to climate change in the southern African region (SHONGWE et al, 2011). The predicted climate changes will threaten some of the current conservation goals such as soil and water conservation, enhanced crop yield and carbon sequestration.…”
Section: Predicted Climate-changing Impacts In Southern Africamentioning
confidence: 99%
“…Predicted changes in the future of African temperatures may be accompanied by a decrease in precipitation, thus altering soil fertility (SHONGWE et al, 2011). Various researchers stressed about high temperatures and precipitation, increasing the rate of soil fertility loss in the form of SOC and worsening nutrient drainage (ELBASIOUNY et al, 2022).…”
Section: Structure and Aggregationmentioning
confidence: 99%
See 1 more Smart Citation
“…Relationships between these different elements have been discussed in several studies. For example, soil properties such as carbon content have been explicitly linked to minimal tillage conservation agriculture methods (e.g., Willcocks and Twomlow, 1993;Bationo et al, 2007;Mchunu et al, 2011;Simwaka et al, 2020). Here, conservation agriculture techniques give rise to changes in soil and water properties, with an increase in porosity resulting in an increased capacity for soil moisture storage, increase in soil carbon stock, and changes in particle size distributions within soils.…”
Section: The Soil-food-water Nexusmentioning
confidence: 99%